Collaborative selling : - Alessandra, Anthony J. (John Wiley & Son, 1993)
Book is a new kind of sales book designed to help you reach exceptional levels of success in today's new sales environment. The world has changed in significant ways and salespeople today are required to have new skills, new attitudes and a new understanding of how to work with their clients. Companies today are participating in a worldwide quantum shift that's particularly acute in the United States